Magnetron Sputtering Construction of Nano-Al Metallized Wood and Its Functional Research - Yanan Wang (MDPI AG, 2021)
The magnetron sputtering method was used to deposit nano-Al film on the wood surface of Pinus sylvestris L. var. mongholica Litv., and the material structure, electrical conductivity, mechanical properties and wetting properties were tested and characterized. When the sputtering time was 60 min, the average cross-grain sheet resistance of metallized wood was 695.9 mΩ, and the average along-grain sheet resistance was 227.2 mΩ. Load displacement decreased by more than 88%,elastic modulus increased by 49.2 times, hardness increased by 46 times andsurface hydrophobic angle was close to 130°. The grain size of the Al film on the wood surface was presented as nanoparticles, and the arrangement was uniform and dense. The results indicate that without any burden on the environment, the use of magnetron sputtering can quickly and efficiently achieve Al metallization on wood surfaces, so that the wood surface can obtain conductivity and hydrophobic properties. The elastic modulus and hardness of the wood surface were improved, the mechanical properties of the wood were effectively improved and the functional improvement of the wood was realized. This study provides a feasible method and basis for the study of the simple, efficient and pollution-free modification of wood.